1957
DOI: 10.1084/jem.106.4.485
|View full text |Cite
|
Sign up to set email alerts
|

Action of X-Rays on Mammalian Cells

Abstract: Survival curves of normal human cells from a variety of tissues exposed to varying doses of x-irradiation have been constructed, which permit definition of the intrinsic radiation sensitivity of the reproductive power of each cell type. The mean lethal dose of x-irradiation for all the cells employed, including those from normal and cancerous organs, those exhibiting diploid and polyploid chromosome number; those from embryonic and adult tissues, including recently isolated cells and cultures wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
4

Year Published

1960
1960
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(70 citation statements)
references
References 11 publications
(22 reference statements)
2
62
0
4
Order By: Relevance
“…Previously, The HRS/IRR response has been studied in SiHa cell line that showed no evidence of HRS [9].The transition dose was found to be 28 cGy for Co60 beam, 25 cGy for 6 MV and 40 cGy for 15 MV photon. The cellular effects of ionizing radiation were described initially by Puck and Marcus [10][11][12]. They first observed the formation of giant cells in HeLa cell colonies following exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, The HRS/IRR response has been studied in SiHa cell line that showed no evidence of HRS [9].The transition dose was found to be 28 cGy for Co60 beam, 25 cGy for 6 MV and 40 cGy for 15 MV photon. The cellular effects of ionizing radiation were described initially by Puck and Marcus [10][11][12]. They first observed the formation of giant cells in HeLa cell colonies following exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Clonogenic survival assays have assessed radiosensitivity and establish predictive models for treatment result [100,101]. In the study of Chiblak and colleagues, human primary glioma stem cells (GSC or brain tumor stem cells) spheroid cultures were established from tumor specimens of six consenting glioblastoma patients [28].…”
Section: The Impact Of Carbon Ion Irradiation On Tumor Stem Cells Carmentioning
confidence: 99%
“…6 In 1932, Desjardins noted that a proportion of irradiated cells exhibited either a temporary inhibition of metabolic activity, or a complete and permanent disintegration, and in 1957, Puck et al demonstrated that the growth of normal fibroblasts in vitro could be inhibited by radiation. 7,8 In the eye, radiation has been shown to inhibit corneal wound healing, with prominent effects on fibroblast proliferation. 9 Radiation therapy has also been utilised as a means of preventing proliferative vitreoretinopathy (PVR).…”
Section: Cellular Effects Of Beta Radiationmentioning
confidence: 99%